2008
DOI: 10.1002/vnl.20140
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polypropylene. I. Surface enrichment of poly(ethylene glycol) on polypropylene/poly(ethylene glycol) blends

Abstract: The enrichment of poly(ethylene glycol) (PEG) on the surface of poly(ethylene glycol)/polypropylene (PEG/PP) blends was investigated by using attenuated total reflection infrared spectroscopy (ATR‐FTIR), contact angle measurement (CDA), and scanning electron microscopy (SEM). The preferred aggregation of the PEG component on the film surface of PP/PEG blends was affected mainly by the content, the molecular weight, and the segregated domains of PEG. Lower content and dies with higher surface energy favored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…10 In this work, extensions of their studies were facilitated by preparation the hydroxyl-and methoxyl-terminated side chain graft copolymer and formation the blend films by melt-cast to avoid the effect of solvent. The results listed in Table III shown that the end group of copolymer had significant effect on surface selectivity.…”
Section: Effect Of Molecular Weight Of Peg In Ppw-g-peg On Surface Enmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In this work, extensions of their studies were facilitated by preparation the hydroxyl-and methoxyl-terminated side chain graft copolymer and formation the blend films by melt-cast to avoid the effect of solvent. The results listed in Table III shown that the end group of copolymer had significant effect on surface selectivity.…”
Section: Effect Of Molecular Weight Of Peg In Ppw-g-peg On Surface Enmentioning
confidence: 99%
“…In our prior research, 10 we have found that PEG can be enriched on the surface of PP and improve its hydrophilicity. However, due to the weak interaction between PEG and PP, PEG was found to be detracted easily from the surface when the modified material was contact with water and other polar chemical solvents.…”
Section: Introductionmentioning
confidence: 98%
“…In our prior work [4], PEG has been used to improve PP hydrophilicity, and we have demonstrated that it can preferably aggregate on the surface of blends films. The transport of PEG in polymer media can be influenced by many factors, such as the annealing temperature and distribution of PEG, as well as the topology of PP amorphous fraction, which affected the surface enrichment of PEG on PP.…”
Section: Introductionmentioning
confidence: 96%
“…Blending with additives which migrate to and alter the surface properties has been recognized as a viable method to overcome those disadvantages . Polymer blending is a cheaper and faster way to induce surface enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…Surface enrichment with PEG increased with an increase in PEG molecular weight but decreased with an increase in concentration. Xu et al . studied the diffusion of PEG in PP.…”
Section: Introductionmentioning
confidence: 99%